Laser-induced fluorescence of free diamondoid molecules. Issue 6 (15th January 2015) - Richter, Robert; Röhr, Merle I. S.; Zimmermann, Tobias; Petersen, Jens; Heidrich, Christoph; Rahner, Ramon; Möller, Thomas; Dahl, Jeremy E.; Carlson, Robert M. K.; Mitric, Roland; Rander, Torbjörn; Merli, Andrea
Abstract : We report on the laser-induced fluorescence of diamondoids in the gas phase. The spectra show well defined vibrational structure, whose complex nature is assigned with the help of TDDFT computations. Abstract : We observe the fluorescence of pristine diamondoids in the gas phase, excited using narrow band ultraviolet laser light. The emission spectra show well-defined features, which can be attributed to transitions from the excited electronic state into different vibrational modes of the electronic ground state. We assign the normal modes responsible for the vibrational bands, and determine the geometry of the excited states. Calculations indicate that for large diamondoids, the spectral bands do not result from progressions of single modes, but rather from combination bands composed of a large number of Δ v = 1 transitions. The vibrational modes determining the spectral envelope can mainly be assigned to wagging and twisting modes of the surface atoms. We conclude that our theoretical approach accurately describes the photophysics in diamondoids and possibly other hydrocarbons in general.